2012
DOI: 10.1210/jc.2012-2669
|View full text |Cite
|
Sign up to set email alerts
|

Low SGK1 Expression in Human Adrenocortical Tumors Is Associated with ACTH-Independent Glucocorticoid Secretion and Poor Prognosis

Abstract: Context:Using single-nucleotide polymorphism analysis, we observed allelic loss of the gene for serum glucocorticoid (GC) kinase 1 (SGK1), a GC-responsive kinase involved in multiple cellular functions, in a subset of cortisol-secreting adenomas.Objective:Our objective was to analyze SGK1 expression in adrenocortical tumors and to further characterize its role in ACTH-independent cortisol secretion, tumor progression, and prognosis.Design and Setting:Gene expression levels of SGK1, SGK3, and CTNNB1 (coding for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 39 publications
(67 reference statements)
2
29
1
Order By: Relevance
“…These data suggest that other mechanisms than tumor proliferation activity have to be taken into account to support the association between hypercortisolism and tumor aggressiveness. For instance, it was recently suggested that SKG1 protein expression was inversely associated with cortisol hypersecretion and that low SGK1 represents a negative prognostic factor in ACC (20). In addition, the chronic exposure to elevated cortisol levels before surgery, leading to immunosuppression, may favour the development of micrometastases.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that other mechanisms than tumor proliferation activity have to be taken into account to support the association between hypercortisolism and tumor aggressiveness. For instance, it was recently suggested that SKG1 protein expression was inversely associated with cortisol hypersecretion and that low SGK1 represents a negative prognostic factor in ACC (20). In addition, the chronic exposure to elevated cortisol levels before surgery, leading to immunosuppression, may favour the development of micrometastases.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, high JAG1 expression correlates with longer DFS and OS in ACC ); • matrix metalloproteinase type 2 (MMP-2) contributes to mediate the process of extracellular matrix degradation by cancer cells. Overexpression of this enzyme involved in metastatic invasion is associated with reduced DFS and OS (Volante et al 2006); • staining for phospho-histone H3, a marker for mitotic cells, was shown to have a borderline correlation with OS in ACC, which was less significant than mitotic count (Duregon et al 2014a); • low expression of serum glucocorticoid kinase 1 (SGK1), an ubiquitous serine/threonine kinase regulated by growth factors, is correlated with shorter OS in ACC (Ronchi et al 2012); • Steroidogenic Factor-1 (SF-1) is a transcription factor, belonging to the nuclear receptor superfamily, that has an essential role in the development of adrenal glands and gonads (Lalli 2010). SF-1 expression is a hallmark of ACT and its higher expression levels in ACC are associated with reduced DFS and OS (Sbiera et al 2010, Duregon et al 2013b.…”
Section: Immunohistochemical Markers Improve Prognostic Assessment Inmentioning
confidence: 99%
“…Cycling conditions were 3 min at 95 8C followed by 50 cycles of 30 s at 95 8C, 30 s at 60 8C, and 30 s at 72 8C. Using the DCT method (Pfaffl 2001), the gene expression levels were normalized to those of b-actin, as previously described (Ronchi et al 2012).…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Immunostaining for b-catenin Immunohistochemistry for b-catenin had been previously performed on the present TMAs, and the results have already been published elsewhere (Gaujoux et al 2011, Ronchi et al 2012. In brief, primary antibody was provided by BD Bioscience (1:400; San Jose, CA, USA), and the nuclear staining (representative of b-catenin pathway activation) was assessed as previously described (Gaujoux et al 2011).…”
Section: Immunohistochemistrymentioning
confidence: 99%